A decision support tool for container terminal optimization within the berth subsystem - Stojaković, Maja; Twrdy, Elen (Transport, 2016)
The article deals with a current problem faced by all ports: how to enable container terminals to keep up with the development of container ships, which, due to economies of scale, are constantly increasing in size. One solution that can help small container ports solve this problem is a use of a Decision Support Tool (DST). The DST is based on simulations and identifications of the container terminal components that require optimization for the reception of the desired ship size in a given port. It consists of the six parts of the terminal that define the operational ship-to-shore system that determines the quality of service when a ship is in the port. A DST was tested on the real data of twelve Mediterranean container terminals. Special focus was made on the optimization possibilities of the container terminal in the port of Koper.First published online: 14 Jan 2015